Perspektif Dalam Seni Lukis Tradisi Indonesia - Agung Purnomo (Gelar : Jurnal Seni Budaya, 2007)
Traditional painting Indonesia like wayang beber and of a kind represent  one of form "genius local" a success expand according to requirement a period of  the Cultural product tidy efficient considerabfy practical and with elements which, is  easy to be arrested and permeated to later, then digested by space think its prop  socie(y of that moment.Visual form of traditional painting of The Indonesia it careful there is an  problems hit is "in perpective" because in laying open form an obyek do not seen  realisitis as perception of human being to real obyek-obyek. To remove "picture"  natural and above its contents an media as area draw realisticallY and have "  dimension to three" needed by knowledge hit is in perpective.Do not there are in perpective element at traditional painting ~l rasse  Indonesia by elementary matter about  way of perceiving an obyek which thry see is  everydqy. Way of idioplasitik approach so central form the condition of think concept  in creating a painting, so that thry are in paint crystal clear take no account of in  perpective element which is often used in visioplastis think frameworkKeyword: Art Paint Tradition, Perspektif